2017
DOI: 10.2135/cropsci2016.12.1028
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mips1, lpa1, and lpa2 Alleles for Low Phytic Acid Content on Agronomic, Seed Quality, and Seed Composition Traits of Soybean

Abstract: Soybean [Glycine max (L.) Merr] is an important agronomic crop around the world, used largely for animal feed. However, ∼75% of the phosphorus (P) in soybean grain is in the form of phytic acid (PA) or phytate, the cation salt form of PA, which cannot be digested by monogastric and agastric animals including swine, poultry, and aquacultural animals, leading to decreased field efficiency and environmental detriment due to P runoff. Soybean lines have been developed with a reduced PA content using mutant alleles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…Compared to this study, the triple mutants from Averitt et al [48] showed higher sucrose (8.25%), lower raffinose (0.86%) and lower stachyose (3.69%) levels; however, only phytate and raffinose levels were significantly different from the mips mutant. Despite the fact that the lowest phytate level (ranging from 0.227-4.864 mg g -1 ) was attained for triple mutant in Averitt et al [48], it was not significantly different from mrp-l/mrp-n mutant, and this observation is consistent with the current study. Different seed phytate levels of triple mutants in these two studies could be due to dissimilarities in the genetic backgrounds of the parental lines used in two studies.…”
Section: Plos Onecontrasting
confidence: 94%
See 2 more Smart Citations
“…Compared to this study, the triple mutants from Averitt et al [48] showed higher sucrose (8.25%), lower raffinose (0.86%) and lower stachyose (3.69%) levels; however, only phytate and raffinose levels were significantly different from the mips mutant. Despite the fact that the lowest phytate level (ranging from 0.227-4.864 mg g -1 ) was attained for triple mutant in Averitt et al [48], it was not significantly different from mrp-l/mrp-n mutant, and this observation is consistent with the current study. Different seed phytate levels of triple mutants in these two studies could be due to dissimilarities in the genetic backgrounds of the parental lines used in two studies.…”
Section: Plos Onecontrasting
confidence: 94%
“…These findings confirm the interaction of MIPS and MRP genes in regulating phytate and RFO biosynthesis pathways in soybean. The MIPS and MRP gene interactions were previously studied using soybean breeding lines originating from V03-5901 (mips) x 04-05N32 (mrp-l/mrp-n) cross [48]. Compared to this study, the triple mutants from Averitt et al [48] showed higher sucrose (8.25%), lower raffinose (0.86%) and lower stachyose (3.69%) levels; however, only phytate and raffinose levels were significantly different from the mips mutant.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…The loss in mineral element concentration and dry matter of cotyledons are related to phytic acid degradation. Phytic acid accounts for 1%–8% of the dry weights of legume seeds (Averitt et al., 2017), during germination, it is broken down by enzyme phytase in a hydrolysis reaction, releasing Pi, metal ions, and myo -inositol for use by the growing individual.…”
Section: Discussionmentioning
confidence: 99%
“…The phytate content of each sample was determined using an indirect Fe colorimetric method as reported in previous studies (Burleson et al, 2012; Averitt et al, 2017). Briefly, 0.5 g of soybean powder was extracted with 10 mL of 0.5 M HCl.…”
Section: Methodsmentioning
confidence: 99%